2019
DOI: 10.1080/14992027.2019.1683626
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of identity: understanding the experiences of adults with hearing loss who use hearing aids

Abstract: Objective: We aimed to determine the identities that adults with hearing loss construct when telling stories about their experiences with hearing loss and hearing aids. Determining and understanding these identities is important because research shows that who a person believes themselves to be has implications for how they approach their healthcare, along with their emotional and physical wellbeing. Design: We employed a qualitative narrative approach. We then used thematic narrative analysis to identify emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…While our study also revealed subthemes that permeated parents’ stories and have yet to emerge from the early HL screening and identification literature (i.e., medical expenses and health coverage, parent-to-parent support, and mom guilt). In this regard, the present study supports newer research that illustrates the importance and value of personal narratives in audiological practice (e.g., Steinberg et al 2007; Barker et al 2020, 2021; Ritter et al 2020). Furthermore, the present findings revealed important moments early on in families’ pediatric HL journeys when providers could intervene via enhanced family-centered approaches to care—something parents themselves have divulged as important.…”
Section: Discussionsupporting
confidence: 88%
“…While our study also revealed subthemes that permeated parents’ stories and have yet to emerge from the early HL screening and identification literature (i.e., medical expenses and health coverage, parent-to-parent support, and mom guilt). In this regard, the present study supports newer research that illustrates the importance and value of personal narratives in audiological practice (e.g., Steinberg et al 2007; Barker et al 2020, 2021; Ritter et al 2020). Furthermore, the present findings revealed important moments early on in families’ pediatric HL journeys when providers could intervene via enhanced family-centered approaches to care—something parents themselves have divulged as important.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, these findings not only revealed that HA users vary in their experiences with HAs, but also that the reasons for HA non-use might be more complex and extend beyond issues of general satisfaction and perceived device-centric barriers as previously noted [3,17]. In other words, Barker and colleagues' [15] research points to the importance of understanding why people choose not to wear their HAs, instead of assuming a dichotomous experience between people who are consistent users versus people who are not. Given the mismatch between provider and patient perceptions and the complexity surrounding HL diagnosis and HA use, direct accounts from HA non-users could provide an imperative perspective that could serve to help hearing healthcare providers understand why the HAs they prescribe are not being used.…”
Section: The Varying Experience Of Ha Usersmentioning
confidence: 53%
“…One potential reason for this disconnect is that not all people with HL have the same experience with HAs. Barker, Scharp, Long, and Ritter [15] recently employed a narrative approach to uncover the identities of adults with HL who reported consistently using their HAs. Specifically, in their qualitative study, they used thematic narrative analysis (TNA) [16] and analyzed narratives from HA users (N = 30).…”
Section: The Varying Experience Of Ha Usersmentioning
confidence: 99%
“…Different individuals give different psychological reactions to hearing impairment and some people consider hearing impairment as a part of their identity 22 . In the present study, no difference was found between the hearing‐impaired patients and normal hearing individuals in terms of the ability to bounce back, recover and return to previous functionality evaluated with BRS during Covid‐19.…”
Section: Discussionmentioning
confidence: 99%